Impact of climate change on solar monofacial and bifacial Photovoltaics (PV) potential in Qatar. (August 2022) - Tahir, Furqan; Baloch, Ahmer A.B.; Al-Ghamdi, Sami G.
Abstract: The considerable growth of the renewables' shares in the energy market paves the way towards United Nations Sustainable Development Goal 7. Solar photovoltaics (PV) are more economically viable amongst other renewables because of their lower, easier installation and reliability. However, the PV, like other renewables, is more vulnerable to climatic conditions. Currently, the monofacial leads the PV market; however, it is expected that the bifacial PV will be dominant as it offers more energy yield at a lower cost. It is thus crucial to analyze the PV performance concerning climatic conditions. The merits of this study include: (i) the performance of bifacial PV for the climate change scenarios is analyzed, which is lacking in the literature; (ii) detailed monofacial and bifacial PV mathematical models are developed to estimate the PV output; and (iii) the comparison is made between monofacial and bifacial PVs performance and their dependence on climatic conditions. The climate model is used to predict the ambient conditions for the years 2050 and 2080. The average hourly responses of solar irradiance and energy yield are presented and analyzed.